Reclaiming Spirit in the Black Faith Tradition - Hicks, D. author. aut Link
XVIII, 233 p.
Keywords: This work attempts to uncover the function of religion for those degraded on the basis of race. Accordingly, Recalibrating Spirit reveals the role of religion in critical reflection on and active protest against negative assertions about racial identity in general, and the abuse of black life in particular.